Pengaruh Rasio C:N Dan Panjang Gelombang Cahaya Terhadap Peningkatan Kandungan Karbohidrat Chlorella SP Dengan Memanfaatkan Limbah Cair Hotel - Sri Indira Puspa Pertiwi; Shinta Elystia; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Carbohydrate content in microalgae can be used as raw material for producing biofuels. Microalgae need nutrients such as carbon and nitrogen also light for their growth. Nutrient source can be obtained from wastewater, such like hotel wastewater. The objective of this study was to determine the best condition for Chlorella sp producing high carbohydrate content by varying the C:N ratio 100:7, 100:13, 100:32 and the light wavelength using a white light color (380-750 nm), blue (450-495 nm), green (495-570 nm), and red (620-750 nm). The experiment was conducted at room temperature under 2000 lux illumination for 15 days. The results showed that Chlorella sp produced the highest carbohydrate content (45,77 mg/l) under C:N ratio 100:7. Moreover, when algae was cultivated under different light wavelength showed that Chlorella sp has grown better and produced more carbohydrate content (48,39 mg/l) under blue light (450-495 nm) when compared to the other types of light. Keywords: Chlorella sp, carbohydrate, C:N ratio, light wavelength